The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00702-014-1345-5
|View full text |Cite
|
Sign up to set email alerts
|

Disease duration of episodic migraine correlates with modified amplitudes and habituation of contingent negative variation

Abstract: Cortical habituation in episodic migraine patients without medication overuse headache (MOH), recorded by contingent negative variation (CNV), is often reduced compared with healthy controls. There is evidence that with longer duration of migraine disease (DOD) amplitudes and habituation of CNV become progressively abnormal. The aim of the study was to examine habituation characteristics of contingent negative variation in episodic migraine patients suffering from short- and long-lasting migraine compared to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 35 publications
5
29
1
1
Order By: Relevance
“…A recent study reported a similar habituation pattern for the N1 orienting and N2b components to deviant tones in patients and matched controls . Habituation deficits have also been reported for the contingent negative variation CNV; in particular the initial (or early) CNV, which reflects the orienting properties of a warning stimulus in an active paradigm, was found increased in migraine . P300 (P3a and/or P3b) responses elicited by various paradigms also showed a deficit of habituation but not systematically .…”
Section: Alteration Of Habituation and Attention To Sensory Inputs Inmentioning
confidence: 65%
See 4 more Smart Citations
“…A recent study reported a similar habituation pattern for the N1 orienting and N2b components to deviant tones in patients and matched controls . Habituation deficits have also been reported for the contingent negative variation CNV; in particular the initial (or early) CNV, which reflects the orienting properties of a warning stimulus in an active paradigm, was found increased in migraine . P300 (P3a and/or P3b) responses elicited by various paradigms also showed a deficit of habituation but not systematically .…”
Section: Alteration Of Habituation and Attention To Sensory Inputs Inmentioning
confidence: 65%
“…74,75 Habituation deficits have also been reported for the contingent negative variation CNV; in particular the initial (or early) CNV, which reflects the orienting properties of a warning stimulus in an active paradigm, was found increased in migraine. [76][77][78][79] P300 (P3a and/or P3b) responses elicited by various paradigms also showed a deficit of habituation 73,80-82 but not systematically. 74 Mismatch negativity (MMN) habituation has been reported as deficient in a first study, 104 but not in a more recent one.…”
Section: Alteration Of Habituation and Attention To Sensory Inputs Inmentioning
confidence: 95%
See 3 more Smart Citations